Sexuality - Nye, Robert A. (Oxford University Press, 1999)
Sexuality has always been an obsessive human concern; it has often been the real subject of cultural, religious, and political discourses that did not dare to mention it or did not have the language for addressing it directly. We now possess both the language and the cultural temerity to discuss sexuality as straightforwardly as we like, and with a frankness that would have shocked people a few decades ago. It now seems impossible to contemplate human happiness without some measure of sexual fulfilment, although that remains a notoriously elusive and negotiable ideal. Nor is it possible now to think about our identities or the identities of others without factoring in sexual tastes and orientation. The central message of this book is that we are unlikely to understand the promise or the limits of our contemporary sexualities unless we understand those of the past. Robert A. Nye's Oxford Reader is intended to be used on the wide ranges of undergraduate courses which address issues of human sexuality: courses taught in departments of history, women's studies, medical history, sociology, gay and lesbian studies, anthropology, religion, and literary studies, as well as in professional programmes such as medicine, public health, clinical psychology, social work, and law. Part I of the Reader forms a chronological narrative of the development of thinking about sexuality from the ancient Greeks to the present. Part II discusses nineteenth-century investigation of phenomena such as hysteria, prostitution, fetishism, and exhibitionism. Part III brings together contemporary conceptions of the sexual body, and Part IV addresses the issue of whether the sexual revolution of the late sixties and seventies has brought about a profound and permanent change in the sexual landscape of western civilization.